Analysis of hand techniques in karate - Mudric, R.; Rankovic, V. (Sport Science & Practice, 2016)
This paper deals with the issue of hand techniques in karate, which describe and represent the essence of both the former self-defence skills and today`s sports karate. Regardless of the methodological and practice system these techniques are taught within and applied (with the open hand or the fist and with a number of striking surfaces in application), they are very attractive and play an important role. The force that is expressed in the application of these techniques carried out with bare hands is fascinating, especially in the demonstration of skills (when breaking various items), while in sports karate they are very useful and have a dominant role in scoring. This paper analyzes the techniques from the methodological, biomechanical and technical tactical points of view, showing the results of scientific research and their temporal characteristics and processes that describe and affirm them as the structural elements of the attack, which in modern sports karate play a dominant role. The displayed techniques are illustrated with appropriate illustrations, diagrams and tables